From Memory to History : Television Versions of the Twentieth Century - Cullen, Jim. (New Brunswick : Rutgers University Press, 2021)
"History is a subject we all learn in school, some of us with more enthusiasm than others. But the way most of us know history-experience it, absorb it, apply its lessons to make sense of our everyday lives-is through popular culture. And no medium of popular culture has been more pervasive in offering Americans a vision of their country in the past century than television. Television has played an especially important role in the interpretation-and reinterpretation-of collective memory, which is to say the events that were experienced first- or second-hand but which have since receded into the past. From Memory to History examines the way TV shows of the past fifty years have depicted US society in the last century. The book examines how a series of events in the past hundred years-from the advent of Prohibition to the advent of the Internet-were portrayed in some of the most beloved shows of all time, among them The Waltons, M*A*S*H, and Mad Men. But the book does more than that. It also explains how any given TV show is at least as important a historical artifact of the time it was made as it is the time it depicts. So it is, for example, that we see how That ''70 Show reveals a lot about the 1990s in the process of telling a story about the 1970s. Or How Hogan's Heroes, a (somewhat bizarre, in retrospect) sitcom about a German concentration camp in World War II, almost despite itself, reveals underlying anxieties about Civil Rights and the Vietnam War in its hermetically sealed episodes. Or how The Americans valorizes the outcome of a Cold War that was a good deal more uncertain than it was in the 1980s, when the series is set. Each of the book's seven chapters offers context for a show's setting, the show's interpretive argument in the moment it was made, and how both look from the perspective of the 2020s. Here, truly, is history in three dimensions. Lively, informative, and incisive, From Memory to History will help you look at television, the American Century, and the times in which you are living in an intriguing new light"--
Frontmatter -- CONTENTS -- INTRODUCTION Television's History -- CHAPTER 1 LEFT TO THE RIGHT The Waltons as a 1970s Version of the 1930s -- CHAPTER 2 CAMP HISTORY Hogan's Heroes as a 1960s Version of the 1940s -- CHAPTER 3 A FUNNY WAR M*A*S*H as a 1970s Version of the 1950s -- CHAPTER 4 DREAM ADVERTISEMENT Mad Men as a 2000s Version of the 1960s -- CHAPTER 5 WE'RE ALL ALL RIGHT That '70s Show as a 1990s Version of the 1970s -- CHAPTER 6 DOMESTIC FRONT The Americans as a 2010s Version of the 1980s -- CHAPTER 7 PROGRAMMING HOPE Halt and Catch Fire as a 2010s Version of the 1990s -- CONCLUSION Visualizing the Future of the Past -- ACKNOWLEDGMENTS -- NOTES -- INDEX -- ABOUT THE AUTHOR
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Television programs -- United States -- History -- 20th century; Television and history -- United States; National characteristics, American; History on television; Television -- Social aspects -- United States; United States -- Civilization -- 20th century; Television broadcasting -- Social aspects -- United States; Émissions télévisées -- États-Unis -- Histoire -- 20e siècle.; Télévision et histoire -- États-Unis.; Histoire à la télévision.; Télévision -- Aspect social -- États-Unis.; États-Unis -- Civilisation -- 20e siècle.; PERFORMING ARTS / General; Civilization; History on television; National characteristics, American; Television and history; Television programs; Television -- Social aspects; United States; 1900-1999; television, tv, film, The Waltons, seventies, Mad Men, That 70's Show, 70's, 30's, 2010s, Nineties, tv shows, television shows, cable, United States, popular culture, MASH, How Hogan's Heroes, sitcom, The Americans, series, entertainment, programming, cable tv, channel, network, family sitcom, broadcast, Twentieth Century; History